A sex-sensitive LC-MS/MS method with isotopic internal standard for prazosin bioequivalence: bridging precision medicine and generic drug policy in China - Chen, Hui; Guo, Junping; Zhu, Zhenyu; Huang, Xiaomei; Guo, Jincai (Frontiers in Pharmacology, 2025)
ObjectiveTo develop a rapid, sensitive, and high-throughput liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for prazosin quantification in human plasma, validate its application in bioequivalence studies, and investigate sex-specific pharmacokinetic differences in a Chinese population.Materials and methodsPlasma samples were processed by protein precipitation with methanol and analyzed using a Waters ACQUITY UPLC® HSS T3 column. Prazosin-d8 was used as an isotopic internal standard (IS) to enhance quantification accuracy. Chromatographic separation was performed with methanol (A) and 0.1% formic acid in water (B) as the mobile phases, using gradient elution at 0.35 mL/min. Quantification was achieved using positive ionization mode with multiple reaction monitoring (MRM) transitions of m/z 384.2→95.0 for prazosin and m/z 392.2→95.0 for IS.ResultsThe method demonstrated excellent linearity (0.1000–30.00 ng/mL, LLOQ: 0.1000 ng/mL), surpassing the sensitivity of prior methods. Bioequivalence analysis confirmed that the 90% confidence interval (CI) for AUC0-24, AUC0-∞, and Cmax geometric mean ratios fell within the regulatory acceptance range (90.00%–111.11%). Sex analysis revealed significantly higher AUC0-24 (+48%) and AUC0-∞ (+46%) medians in females (n = 4) than in males (n = 16) (P < 0.05), suggesting potential sex-based differences in prazosin pharmacokinetics.ConclusionThis study establishes the first LC-MS/MS method integrating isotopic IS and sex-specific pharmacokinetic profiling for prazosin, offering regulatory-compliant bioequivalence validation and insights into precision dosing strategies. These findings support China’s generic drug policy and highlight the need for sex-stratified pharmacokinetic evaluations in bioequivalence assessments.Clinical trial registration numberChiCTR2100050626.